1974
DOI: 10.1073/pnas.71.8.3059
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Morphology and Fine Structure of CHO (Chinese Hamster Ovary) Cells Following Enucleation

Abstract: Chinese hamster ovary cells grown in monolayer culture and exposed to cytochalasin B were enucleated by centrifugation. Thereafter, the karyoplasts (the nucleated parts obtained from the bottoms of the centrifuge tubes) and the cytoplasts (the enucleated cytoplasmic parts attached to the coverslips) were allowed to recover and subsequently were examined by scanning and transmission electron microscopy. Cytochalasin B causes rapid and dramatic changes in the morphology of vertebrate cells growing in monolayer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Karyoplasts can contain ribosomes, occasional mitochondria and a few fragments of the endoplasmic reticulum [14], but lack centrioles, microtubules and Golgi apparatuses [15]. These characteristics need to be monitored carefully when karyoplasts are generated for the production of nuclear transferred offspring.…”
Section: Resultsmentioning
confidence: 99%
“…Karyoplasts can contain ribosomes, occasional mitochondria and a few fragments of the endoplasmic reticulum [14], but lack centrioles, microtubules and Golgi apparatuses [15]. These characteristics need to be monitored carefully when karyoplasts are generated for the production of nuclear transferred offspring.…”
Section: Resultsmentioning
confidence: 99%
“…1b-c and 4a). Minor differences in the cell surface appearance observed at 1 dpp may be attributed to variations in cell cycle stage, protein expression levels, and metabolism of individual cells [55,58]. After 2 dpp, most of the ScN2a cells exposed a slightly increased surface roughness (Fig.…”
Section: Fibrillar Network Form On Top Of Murine Neuroblastoma Cellsmentioning
confidence: 99%
“…By judicious choice of the parental cell types and the use of a variety of staining techniques, such reconstituted cells can be produced in large numbers and definitively identified immediately after fusion (8)(9)(10)(11). These cells, having a minimal contribution of cytoplasm from the nuclear donor cell type (12)(13)(14)(15), would appear to be excellent systems for investigating the interaction of cytoplasm and nucleus in determining a variety of cellular properties and events, including cell shape and cytoarchitecture and genome replication and expression. However, analyses of both reconstructed and cybrid cells performed so far have indicated that, except for a few instances (16)(17)(18)(19)(20)(21), exposure to a foreign cytoplasm has little long-term effect on a transplanted nucleus.…”
mentioning
confidence: 99%